Adverse drug events associated with insulin glargine: a real-world pharmacovigilance study based on the FAERS database - Wang, Tongtong; He, Gefei; Xiong, Wan; Huang, Juanjuan (Frontiers in Pharmacology, 2025)
BackgroundInsulin glargine is a long-acting drug and the first synthetic insulin to mimic human metabolism. The safety of insulin glargine in the real world remains to be further investigated. This study aims to analyze insulin glargine-related adverse events (ADEs) to guide its safe clinical use.MethodsThis study collected ADE reports from the FDA Adverse Event Reporting System (FAERS) between the first quarter of 2004 and the third quarter of 2024, where insulin glargine was identified as the primary suspect drug. Four disproportionate analytical methods were employed to analyze positive signals for drug-related ADEs, including the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS). The study also describes the time to onset of ADEs and uses the Weibull distribution to analyze the temporal trend of ADEs occurrence over time.ResultsThis study included 97,350 ADE reports, containing 228,258 ADEs, and identified 130 ADEs with positive signal. The study confirmed several known ADEs, such as hypoglycemia, injection site pain and acquired lipodystrophy. Additionally, several unexpected ADEs were identified, including pancreatic neoplasm, medullary thyroid cancer, and bone marrow tumor cell infiltration. 28.13% of ADEs occurred within the first month. The Weibull distribution indicated that the occurrence of ADEs decreased over time.ConclusionThis study explored the real-world safety of insulin glargine and revealed several unexpected ADEs. These findings provide new insights into the safety profile of insulin glargine for clinicians.”